Role of non-invasive markers in prediction of esophageal varices and variceal bleeding in patients of alcoholic liver cirrhosis from central India - Kothari, Harit Goverdhan; Gupta, Sudhir Jagdishoprasad; Gaikwad, Nitin Rangrao; Sankalecha, Tushar Hiralal; Samarth, Amol Rajendra (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Alcohol is the leading cause of liver cirrhosis, which results in portal hypertension and subsequently, culminates into esophageal varices and esophgeal variceal bleeding. Esophagogastroduodenoscopy is gold standard for diagnosis of varices. Non-invasive markers based on clinical, laboratory & ultrasonographic parameters can be utilised for prediction of risk of esophageal varices & variceal bleed in alcoholic cirrhosis from central India. Materials and Methods: This was a cross sectional observational study. Child Turcot Pugh scores, MELD, AST ALT Ratio(AAR), AST Platelet Ratio Index(APRI), FIB-4 index and Platelet count-Spleen diameter(PC/SD) ratio were calculated for all patients and correlated with esophagogastroduodenoscopy findings. Short term follow up was done for variceal bleeding. Results: Total 202 male patients were included with mean age of 43.77±9.95 years. 188(93%) patients had esophageal varices. 61(30.19%) patients had variceal bleeding. On univariate analysis platelet count, APRI, spleen bipolar diameter, and PC/SD ratio were significantly associated with varices. For prediction of esophageal varices, only PC/SD ratio was significant and showed area under the curve of 65.6% at cut-off of <997. CTP score, FIB-4, APRI, and PC/SD ratio were significant for variceal bleeding. At cut-off <985 PC/SD ratio had sensitivity of 82% and specificity of 63% with AUC of 78% for prediction of variceal bleeding. Also, FIB-4 and APRI had diagnostic accuracy of 64% and 61% with AUC of 74% and 72% respectively for bleed. Conclusion: FIB-4 and PC/SD may be useful among armamentarium of non-invasive markers for predicting esophageal varices and risk of variceal bleeding in alcoholic liver cirrhosis.